Guía para la revisión de diseños de puentes de la Unidad Ejecutora del Primer Programa de Infraestructura Vial (UE-PIV 1) - Gómez-Bermúdez, Aarón Josué (Instituto Tecnológico de Costa Rica, 2017)
Currently the development of road infrastructure in Costa Rica is having a significant boom due to the need to improve the service level of the national red road infrastructure. Vehicle bridges call for a large part of these works, consecuently in this project the purpose is the implementation of a protocol to carry out the bridge design review that the administration has to undertake to approve these designs and fulltill the goal of improving the national road network. In order to achieve the propossed objective, different activities were done, such as the collection, analysis and unification of information in the UE-PIV 1 of Conavi, in order to obtain the final product. What was finally obtained is the Guide for the revision of bridge designs, which includes the necessary aspects to verify the designs submitted by the contractors to the administration, covering calculation reports, technical studies and construction plans, with the purpose to make the review more efficient.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2017.
Keywords: Puentes; Infraestructura; Metodología; Verificación; Planos